2021
DOI: 10.1093/cid/ciab288
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hospitalized and Severe Dengue Cases Over the 6 years of Follow-up of the Tetravalent Dengue Vaccine (CYD-TDV) Efficacy Trials in Asia and Latin America

Abstract: Background CYD-TDV, a live, attenuated, tetravalent dengue vaccine, has been approved for the prevention of symptomatic dengue in previously dengue exposed individuals. This post-hoc analysis assessed hospitalized and severe virologically-confirmed dengue (VCD) over the complete 6-year follow-up of three CYD-TDV efficacy studies (CYD14, CYD15 and CYD23/CYD57). Methods The main outcomes were hazard ratios (HRs) for hospitalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…We selected performance age cutoffs on the basis of evidence of CYD-TDV safety and efficacy in individuals aged 9 years or older and in those aged 6-8 years. 9 years is the lower age limit for vaccination in most countries where CYD-TDV is approved, and evidence published in 2021 suggested a positive benefit-risk profile in children aged 6-8 years as well; 16 these subgroup analyses were prespecified for practical reasons to inform policy makers on the safety and accuracy of the new IgG RDT for pre-vaccination screening. For sensitivity, specificity, and predictive values, the 95% CIs were estimated using the exact binomial method (Clopper-Pearson method).…”
Section: Discussionmentioning
confidence: 99%
“…We selected performance age cutoffs on the basis of evidence of CYD-TDV safety and efficacy in individuals aged 9 years or older and in those aged 6-8 years. 9 years is the lower age limit for vaccination in most countries where CYD-TDV is approved, and evidence published in 2021 suggested a positive benefit-risk profile in children aged 6-8 years as well; 16 these subgroup analyses were prespecified for practical reasons to inform policy makers on the safety and accuracy of the new IgG RDT for pre-vaccination screening. For sensitivity, specificity, and predictive values, the 95% CIs were estimated using the exact binomial method (Clopper-Pearson method).…”
Section: Discussionmentioning
confidence: 99%
“…Vaccine efficacy against hospitalization decreased from 91% (95% CI: 80%-96%) during the first and second years combined after vaccination to 56% (95% CI: 25%-78%) during the fifth and sixth years combined after vaccination. Vaccine efficacy against hospitalization remained significant throughout the 6-year follow-up period (54).…”
Section: Vaccine Efficacymentioning
confidence: 91%
“…After six years, they found that the CYD-TDV vaccine protected against severe and hospitalized VCD in children aged nine years and more who were seropositive. The vaccine also demonstrated good efficacy in seropositive children aged six to eight during most follow-up years [ 25 ]. These results seem to confirm the findings made by Arredondo-García et al in 2018, who demonstrated the efficacy of Dengvaxia® in the same age range.…”
Section: Reviewmentioning
confidence: 99%